The Role of Job Satisfaction in Mediating the Effects of the Digital Work Environment, Organizational Culture, and Work Commitment on Banking Employee Performance - Rezky Ratnasari Taufan A; Taupan Taupan; Sian Linda Lerebulan; Moh Zulkifli Murfat (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to examine the effects of the digital work environment, organizational culture, and work commitment on employee performance, with job satisfaction serving as a mediating variable in the banking sector in Makassar. Research Method: This study employed a quantitative approach with an explanatory research design. Data were collected from 184 banking employees using purposive sampling techniques. The data were analyzed using covariance-based Structural Equation Modeling (SEM) with the assistance of AMOS to test both direct and indirect relationships among the variables. Results and Discussion: The findings indicate that the digital work environment, organizational culture, and work commitment have positive and significant effects on job satisfaction. Job satisfaction also has a positive and significant effect on employee performance. Furthermore, the digital work environment and work commitment have both direct and indirect effects on employee performance, indicating partial mediation through job satisfaction. In contrast, organizational culture does not directly affect employee performance, but it has a significant indirect effect through job satisfaction, indicating full mediation. Implications: The study highlights the importance of integrating digital transformation initiatives with effective human resource management practices. Banking organizations should focus on creating supportive digital work environments, strengthening organizational culture, and fostering employee commitment in order to enhance job satisfaction and improve overall performance.